Environmentally friendly surface treatments used to avoid algal colonization on mortars - Correa, María Verónica (2024)
Biodeterioration is a major problem with construction materials. Presence of biofilm, biofouling, or biopatina, causes decomposition processes of the material both on its surface manifesting as undesirable aesthetic alter ations as well as within the material. In this study, two environmentally friendly treatments were evaluated in an attempt to prevent the growth of phototrophic biofilms on mortar surfaces. Those surfaces were treated using a water-based solution with surfactants with and without thymol 1 %. The algaecide effect was evaluated, leaving a set of samples without treatment as a control of algae growth. The inoculum used in the tests was an algae community isolated from the mausoleum studied. Samples were inoculated with this community and they were incubated under controlled photoperiod and temperature conditions for 30, 60 and 120 days. For surfaces treatments stability assay, other mortars samples were inoculated 30, 60 and 90 days after surface treatments were applied. For surfaces studies were used stereoscopic microscopy, Environmental Scanning Electron Mi croscopy and epifluorescence microscopy, also surface contact angle and colour and bright were measured. Both treatments inhibited algal growth in mortar surfaces. We propose that these surface treatments would be potentially useful for cleaning and preventing phototrophic formation of biofilms on historic buildings.